Thioxanthone Dioxide Triplet States Have Low Oxygen Quenching Rate Constants - Jockusch, Steffen; Kazancioglu, Elif Ozcelik; Karaca, Nurcan; Arsu, Nergis; Landgraf, Stephan; Ogilby, Peter R. (AMER CHEMICAL SOC, 2023)
With few exceptions, triplet excited states of organic molecules, M-3(1), are quenched by ground state molecular oxygen, O-2(X-3 Sigma(-)(g)), with rate constants k(q) greater than similar to 10(9) M-1 s(-1) in fluid solutions. If the energy of the triplet state is above 94 kJ/mol, then such quenching can result in the sensitized production of singlet oxygen, O-2(a(1)Delta(g)). In the interaction between M-3(1) and O-2(X-3 Sigma(-)(g)), the magnitudes of both k(q) and the yield of the O-2(a(1)Delta(g)) depend appreciably on mixing with the M-O-2 charge-transfer state. Here, we report that triplet states of several thioxanthen-9-one-10,10-dioxide derivatives have unusually low k(q) values (as low as similar to 1 x 10(8) M-1 s(-1)) but have quantum yields for the photosensitized production of O-2(a(1)Delta(g)) that approach unity. Because these molecules possess high oxidation potentials (similar to 3.5 V vs SCE), we suggest that charge transfer character in the M-3(1)-O-2(X-3 Sigma(-)(g)) encounter complex is reduced, thereby lowering k(q) while maintaining high O-2(a(1)Delta(g)) yields. These results provide important experimental support for existing models for the quenching of organic molecule excited states by O-2(X-3 Sigma(-)(g)).
Keywords: SINGLET OXYGEN; MOLECULAR-OXYGEN; POLYMERIZATION; SENSITIZATION; FLUORESCENCE; GENERATION; DEPENDENCE; Biophysics; Chemistry